Evaluation of Efficacy and Safety of Latanoprost/Timolol versus Travoprost/Timolol Fixed Combinations for Ocular Hypertension Associated with Uveitis. (2nd January 2017) - Takeuchi, Masaru; Kanda, Takayuki; Taguchi, Manzo; Shibata, Masaki; Mine, Izumi; Sakurai, Yutaka
ABSTRACT: Purpose : To compare latanoprost/timolol (LT) versus travoprost/timolol (TT) fixed combinations for ocular hypertension (OHT) associated with uveitis. Methods : Thirty-six patients (55 eyes) who were treated with LT (28 eyes) or TT (27 eyes) for OHT associated with uveitis were reviewed retrospectively. Intraocular pressure (IOP) and inflammation scores at the initiation of treatment and at the last visit during therapy were analyzed. Results : Although IOP was reduced significantly in both LT and TT groups, the reduction rate was significantly greater with TT group than with LT. The differences in the reduction of IOP between the groups remained significant when the cases were classified into inflammation-induced OHT and steroid-induced OHT. Inflammation score was not exacerbated by LT or TT treatment. Conclusions : Both LT and TT are safe and effective for the treatment of OHT associated with uveitis and greater IOP reduction may be achieved by TT than by LT treatment.